2022
DOI: 10.55684/79.2.1632
|View full text |Cite
|
Sign up to set email alerts
|

Infarto Do Miocárdio Durante a Pandemia De Covid-19: Análise Comparativa Em Cinco Capitais Brasileiras

Abstract: RESUMO – Na tentativa de controle de transmissão da COVID-19, os órgãos de saúde recomendaram isolamento domiciliar, distanciamento social e suspensão de serviços hospitalares não urgentes. Grande parte da população relutou em buscar atendimento médico. A hipótese levantada é que houve redução na incidência de internamentos e aumento na mortalidade por infarto agudo do miocárdio durante a pandemia. Este estudo procurou comparar e analisar a incidência dos internamentos e mortalidade por infarto agudo do miocár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
0
0
2
Order By: Relevance
“…In addition, it is suggested that nurses conduct the nursing process to implement systematic nursing care and identify factors associated with CVR, such as aging, gender, SAH, DM, hypercholesterolemia, smoking, overweight, and PAD (1,5,11) . Differently from our findings, in another study (8) , the daily number of emergency consultations decreased by 45%, non-elective hospitalizations by 50%, and TCA procedures by 29% for treating AMI during the period of social isolation due to the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, it is suggested that nurses conduct the nursing process to implement systematic nursing care and identify factors associated with CVR, such as aging, gender, SAH, DM, hypercholesterolemia, smoking, overweight, and PAD (1,5,11) . Differently from our findings, in another study (8) , the daily number of emergency consultations decreased by 45%, non-elective hospitalizations by 50%, and TCA procedures by 29% for treating AMI during the period of social isolation due to the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study in China showed an increase in the meantime from the onset of AMI symptoms to the first medical contact during the pandemic (7) . In Brazil, a decline in hospitalization rates was identified in an ecological study in five capitals of different Brazilian regions, which identified a decline of 16.15%, from 77.7 hospitalizations per 100 thousand people to 65.15 during the pandemic (8) . The fear of contamination by COVID-19 during medical care made patients stay home, which can lead to death.…”
Section: Page |mentioning
confidence: 99%
“…Na análise de hospitalizações e óbitos nas regiões brasileiras, no estudo de (Cintra et al, 2021;Pelizon et al, 2021).…”
Section: Discussionunclassified
“…Pelizon et al (2021) comparando a incidência de IAM em cinco capitais brasileiras, Manaus, Recife, São Paulo, Curitiba e Campo Grande no período de março de 2019 a fevereiro de 2021, os resultados indicam uma redução. No período que antecede a pandemia as hospitalizações por IAM foram de 14.804, representando 77,70/100.000 habitantes.…”
unclassified